2023
DOI: 10.1186/s12872-023-03155-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D receptor gene polymorphisms (TaqI and BsmI) on the incidence and severity of coronary artery disease: a report from southern Iran

Abstract: Background The association of vitamin D level and vitamin D receptor (VDR) gene polymorphisms with the prevalence of coronary artery disease (CAD) has been evaluated in various studies; however, the reported results were inconsistent. Hence, we aimed to investigate the impact of two VDR gene polymorphisms, TaqI (rs731236) and BsmI (rs1544410), on the incidence and severity of CAD in Iranian population. Methods Blood samples were collected from 118 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The rs731236 polymorphism is associated with increased CAD risk in Pakistani and Croatian populations [ 56 , 57 ]. At the same time, researchers from Spain and South Iran reported no correlation between this polymorphic variant and susceptibility to CAD development [ 58 , 59 ]. Contradictory data have been obtained for the rs1544410 polymorphism— the A allele may have both risky [ 60 ] and protective effects [ 59 ] in relation to CAD development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rs731236 polymorphism is associated with increased CAD risk in Pakistani and Croatian populations [ 56 , 57 ]. At the same time, researchers from Spain and South Iran reported no correlation between this polymorphic variant and susceptibility to CAD development [ 58 , 59 ]. Contradictory data have been obtained for the rs1544410 polymorphism— the A allele may have both risky [ 60 ] and protective effects [ 59 ] in relation to CAD development.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, researchers from Spain and South Iran reported no correlation between this polymorphic variant and susceptibility to CAD development [ 58 , 59 ]. Contradictory data have been obtained for the rs1544410 polymorphism— the A allele may have both risky [ 60 ] and protective effects [ 59 ] in relation to CAD development. In the Spanish population, the rs1544410 polymorphism is not associated with the risk of CAD [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intronic SNPs rs1544410 (G>A) and rs7975232 (A>C), also named BsmI and ApaI, respectively, from the associated restriction enzyme, have been significantly related to low HDL cholesterol and low vitamin D. Homozygotes for the mutated A allele of BsmI resulted in an increased risk of CAD [139]. In other populations, BsmI but not TaqI significantly correlates with the incidence of CAD [140]. Other authors found no relationship between ApaI or TaqI and CAD, while a significant association was reported for another SNP, rs2228570, also known as FokI (A>T,C,G on exon 2) [141].…”
Section: Geneticsmentioning
confidence: 99%